Six-year follow-up of an abstinence-based, food addiction recovery approach to weight management - Thompson, Susan Peirce; Briones, Nadia M.; Blumkin, Aaron; Rabinowitz, Betty A. (Frontiers in Psychiatry, 2025)
IntroductionResearch shows that the average person has a slightly addictive relationship with food, manifesting two or more symptoms of food addiction, and more than one in eight people have clinically diagnosable food addiction. Meanwhile, obesity and food addiction share some neurological mechanisms and are correlated in the general population. Could an abstinence-based approach to food addiction recovery be a viable long-term weight loss or weight maintenance strategy?MethodsThe current study presents six-year retrospective follow-up data from a cohort of participants who started an abstinence-based food addiction recovery program for weight loss in October of 2017. Survey responses from 267 participants were analyzed and compared to baseline self-reported data from six years prior.ResultsAt six years, 71.8% of participants were maintaining greater than 5% weight loss. There was a statistically significant association between sustained weight loss and both current program membership (p<0.001) and degree of adherence to the abstinence-based food plan (p<0.001). Adherence was associated with weight loss outcomes in a dose-response manner. The average sustained weight loss for current members who followed the program was 13.9%.DiscussionIn spite of the methodological challenges with this type of study, the results do suggest the long-term efficacy of a food addiction recovery approach to weight loss. They also help validate the notion that food addiction may be a significant contributor to the multi-factorial etiology of obesity and indicate the need for further research into the viability of abstinence-based food plans as tools for weight management.